Biomarkers and Tourette syndrome: a systematic review and meta-analysis - Jiang, Yanlin; Li, Yuan; Chen, Xi; Zhai, Rui; Peng, Yaqi; Tai, Ran; Zhou, Congxiao; Wang, Junhong (Frontiers in Neurology, 2024)
Objective This research aims to investigate whether peripheral biomarkers might differentiate individuals with Tourette syndrome (TS) from those without the condition. Methods A broad range of databases was searched through November 2022. This study employed a systematic literature review and subsequent meta-analysis of case-control studies that assessed the aberration of biomarkers of patients with TS and controls. Results A total of 81 studies were identified, out of which 60 met the eligibility criteria for inclusion in the meta-analysis. Following a meticulous screening procedure to determine the feasibility of incorporating case–control studies into the meta-analysis, 13 comparisons were statistically significant [CD3+ T cell, CD4+ T cell, CD4+ T cell to CD8+ T cell ratio, NK-cell, anti-streptolysin O antibodies, anti-DNase antibodies, glutamic acid (Glu), aspartic acid (Asp), ferritin (Fe), zinc (Zn), lead (Pb), vitamin D, and brain-derived neurotrophic factor (BDNF)]. Publication bias was found for anti-streptolysin O antibodies. Suggestive associations were evidenced for norsalsolinol (NSAL), neuron-specific enolase (NSE), and S100B. Conclusion In this study, we present empirical evidence substantiating the link between several peripheral biomarkers and the early diagnosis of TS. Larger and more standardized studies are necessary to replicate the observed results, elucidate the specificity of the biomarkers for TS, and evaluate their precision for use in clinical settings.